Knowledge is not power: Learning in polycentric governance systems. - Rittelmeyer, Pamela; Lubell, Mark; Hovis, Meredith; Heikkila, Tanya; Gerlak, Andrea; Pozzi, Tara (Review of Policy Research, 2025)
The link between knowledge and decision‐making in polycentric systems is shaped by the process of collective learning, where policy actors participate in multiple policy forums to acquire, translate, and disseminate knowledge. This article argues that the relationship between learning and participation in polycentric systems differs for actors with executive responsibilities versus specialized staff. Using a mix of quantitative and qualitative data, we show that executive staff are less likely to learn because of their incentives, resources, and position in the system. In contrast, specialized staff are more likely to learn as they form epistemic communities focused on specific policy issues. The different learning experiences of executive versus technical staff contributes to the disjunction between knowledge and power that is a feature of all polycentric systems. Bridging this gap requires institutional arrangements and training to enable the development of trust‐based relationships between decision‐makers, scientists, and other types of specialized knowledge communities.